Dynamics of Vitamin D Metabolism in Maternal–Fetal Dyads. Issue 3 (March 2016) - Hanson, Corrine; Anderson-Berry, Ann; Lyden, Elizabeth; Kaufmann, Martin; Wu, Amy; Elliott, Elizabeth; Lee, Jae-In; Jones, Glenville
ABSTRACT: Objectives: Metabolites of vitamin D in maternal–neonatal dyads remain relatively unexplored. The goal of this study was to evaluate concentrations of 25(OH)D3, 24, 25(OH)2 D3, and 3-epi-25(OH)D3 in maternal–infant pairs at delivery. Methods: Serum samples of maternal and infant cord blood were collected on 131 mother–infant pairs at delivery. Vitamin D metabolites were analyzed in triplicate using liquid chromatography-tandem mass spectrometry. Statistical analysis was conducted using the Fisher exact test, Wilcoxon rank sum test, and Spearman correlation coefficients. Results: Mean 25(OH)D3 concentrations in maternal and cord blood were 32.9 and 18.5 ng/mL, respectively; mean maternal and cord 24, 25(OH)2 D3 were 2.0 versus 1.1 ng/mL, respectively. Absolute concentrations of 3-epi-25(OH)D3 were similar in maternal and cord samples (2.4 vs 2.2 ng/mL), whereas the proportion of the total 25(OH)D as the 3-epimer was 6.5% in maternal samples and 10.5% in cord samples. This suggests that the fetus contributes significantly to 3-epi-25(OH)D3 production. In contrast, the ratio of 25(OH)D3 :24, 25(OH)2 D3 was identical in maternal and cord samples (18.5) suggesting equivalent CYP24A1 activity in mother and fetus. Maternal and cord metabolite levels were highly correlated ( r = 0.78, 0.90, 0.89 for 25(OH)D3, 24, 25(OH)2 D3, and 3-epi-25(OH)D3, respectively, P = 0.001 for all). Serum concentrations of all metabolites were lower in nonwhite infants compared with white infants. Maternal and cord concentrations of 25(OH)D3 were positively associated with birth weight ( r = 0.21, P = 0.02; r = 0.25, P = 0.003, respectively). Conclusions: This data suggests that although maternal and cord concentrations of vitamin D metabolites are highly correlated, regulation of specific vitamin D metabolites in the mother and the neonate may be mediated independently.